Feedback on video skill: A concept analysis - Epstein, Iris; Bertram, Mavoy S.; Lightstone, Elisheva; Pham, Thi Thanh Tuyen; Quach, Lilia; Santos-Macias, Jarinca; Skardzius, Karen (INYI Journal, 2020)
Increasing rates of mental health concerns are seen among youth in post-secondary institutions, particularly those enrolled in clinical-based health programs such as nursing. Nursing students are required to demonstrate skill competence for successful completion of nursing programs. Recent studies show that when students and faculty are engaged in video and audio recording of their own skills or co-creating video skills, many positive outcomes emerge, including a positive influence on their mental health. However, these videos skills are often overlooked by faculty. We explore the concept of "feedback on video skills" and its pedagogical and ethical implications for health and allied health practitioners within the context of flexible learning environments. Walker and Avant’s (2011) concept analysis methodology was used. We identified the quantitative attributes and characteristics of "feedback on video skills" and presented sample cases to illustrate the concept further and guide the design and application of an online feedback video toolbox resource. Feedback is an important dimension of video skill teaching and learning. While faculty (expert) feedback on clinical skills is paramount in nursing education, other forms of feedback can be as valuable. This concept analysis method highlighted quantitative elements of feedback but left gaps in our understanding of the social relations and ethical considerations involved in using videorecorded feedback as a pedagogical tool. We suggest to further consider the use of video-recorded feedback through the lens of socio-technical affordances.